The cold war is over - again - Lynch, Allen, 1955- 17.08.1955- (Westview Press, 1992)
In this book, Allen Lynch challenges the common wisdom that the revolutionary events in Eastern Europe in 1989 and in the Soviet Union in 1991 marked the end of the cold war. Instead, he argues that the cold war was actually resolved by the early 1970s, as evidenced by the tacit acceptance of a divided Germany and Europe. More recent events thus overthrew not the cold war but the post-cold war order in East-West and U.S.-Soviet relations. And--often to their surprise and consternation--leaders of the governments involved must now face formidable new forces created by German unity and nationalism in Eastern Europe and the former Soviet Union, which were contained efficiently--if at times brutally--by the post-cold war order. In its three sections, the book reviews historical, contemporary, and future-oriented themes, respectively. Lynch begins by exploring the deeper logic of the cold war and how it was resolved by the 1970s. He then presents an overview of recent Soviet domestic and foreign policy processes as they affect East-West relations. The concluding section considers the future, with special emphasis on the implications of a fragmented USSR for U.S. foreign policy.